Clinical outcomes of subcutaneous methotrexate in the management of chronic plaque psoriasis - Siddique, Mohammad Rahmat Ullah; Khan, Alauddin; Begum, Sharmin (International Journal of Research in Medical Sciences, 2025)
Background: Chronic plaque psoriasis, also known as psoriasis vulgaris, is the most common form of psoriasis. Subcutaneous methotrexate has been utilized in the management of chronic plaque psoriasis, offering an alternative route of administration to the traditional oral method. The aim of this study was to evaluate the clinical outcomes of subcutaneous methotrexate in the management of chronic plaque psoriasis. Methods: This cross-sectional observational study was conducted in department of dermatology, Bangabandhu Sheikh Mujib medical university, Dhaka, Bangladesh, during the period from November 2023 to May 2024. Total 70 participants were included in this study. Results: The average age of participants was 42.3±11.8 years, with 52.9% males and 47.1% females. Baseline PASI scores averaged 18.5±4.2, indicating moderate-to-severe psoriasis. Mean psoriasis duration was 7.2±3.5 years. Depression (34.3%) was the most common comorbidity, followed by diabetes (15.7%) and hypertension (8.6%). Majority of the participants, 62.86% (n=44), had moderate psoriasis. Nausea (58.9%) was the primary reason for switching from oral to subcutaneous methotrexate, which led to progressive PASI reductions: 32.9% at Week 4, 53.0% at week 8, 69.7% at week 12, and 84.9% at week 16 (p<0.001). Adverse events were mild, with nausea (11.4%) and fatigue (8.6%) being most common. Conclusions: This study demonstrated that subcutaneous methotrexate is a highly effective, safe, and well-tolerated treatment for moderate-to-severe chronic plaque psoriasis.